2003
DOI: 10.2527/2003.8151323x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of substrate and/or neurohormonal mimic on in vitro pancreatic enzyme release from calves postruminally infused with partially hydrolyzed starch and/or casein1

Abstract: Our objectives were to determine the effects of neuroendocrine challenge and substrates on in vitro alpha-amylase and trypsin release in pancreatic tissue collected from Holstein calves (n = 24; 88 +/- 3 kg) abomasally infused for 10 d with tap water (control), partially hydrolyzed starch (SH; 4 g/[kg of BW x d]) and/ or casein (0.6 g/[kg of BW x d]). The caudal portion of the pancreas was removed, rinsed with ice-cold saline, cut into approximately 2 x 2-mm segments, and incubated in oxygenated Krebs Ringer b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Increased dietary protein has been associated with increased plasma CCK in both nonruminants (Konturek et al, 1973;Nishi et al, 2003;Veldhorst et al, 2008) and ruminants (Furuse et al, 1992). Swanson et al (2003) observed direct responses of cattle pancreatic tissues when incubated with caerulein, a CCK analog. Circulating concentrations of CCK were not strongly affected by treatment in Exp.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Increased dietary protein has been associated with increased plasma CCK in both nonruminants (Konturek et al, 1973;Nishi et al, 2003;Veldhorst et al, 2008) and ruminants (Furuse et al, 1992). Swanson et al (2003) observed direct responses of cattle pancreatic tissues when incubated with caerulein, a CCK analog. Circulating concentrations of CCK were not strongly affected by treatment in Exp.…”
Section: Discussionmentioning
confidence: 92%
“…We interpret the increase in ethanol-soluble starch flow and lack of response in small intestinal starch digestion in response to EAA to suggest that luminal hydrolysis of starch via pancreatic α-amylase was increased by EAA, but small intestinal starch digestion was limited by hydrolysis of small-chain oligosaccharides by α-glycohydrolases. Swanson et al (2003) noted that pancreatic tissue from cattle with greater postruminal supplementation of casein had increased responsiveness to CCK and acetylcholine agonists. Hara et al (2001) reported that nonessential AA play an integral role in secretion of α-amylase in rats, and specific nonessential AA can be essential for secretion of α-glycohydrolases by the intestinal epithelium (Schroder et al, 1995;Horvath et al, 1996;Weiss et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several researchers have shown that post‐ruminal or intravenous infusions of α‐amylase products result in decreases of expression (Swanson et al., 2000, 2002a, 2003) and secretion (Call et al., 1975; Walker and Harmon, 1995; Swanson et al., 2002b, 2004) of pancreatic α‐amylase in cattle and sheep. It was hypothesized that excessive RES inhibiting pancreatic α‐amylase secretion may be related to the accumulation of α‐amylase products in the small intestine and in the blood.…”
Section: Discussionmentioning
confidence: 99%